Design and Synthesis of Photoactive Ionic Liquids - Avo, Joao; Cunha-Silva, Luis; Lima, Joao Carlos; Jorge Parola, A. (Organic Letters, 2014)
n/a
Avo, Joao/C-6939-2013; Lima, Joao/F-3658-2010; Lima, Joao Carlos/K-2890-2014; Parola, A. Jorge/F-4048-2010; Cunha-Silva, Luis/A-8765-2012 Avo, Joao/0000-0002-3380-748X; Lima, Joao/0000-0003-0528-1967; Parola, A. Jorge/0000-0002-1333-9076; Cunha-Silva, Luis/0000-0001-9229-1412 3